The critical size of gold nanoparticles for overcoming P-gp mediated multidrug resistance. Issue 31 (17th June 2020) - Jiang, Yuqian; Wang, Zheng; Duan, Wei; Liu, Lingyan; Si, Mahan; Chen, Xiaoyuan; Fang, Chen-Jie
Abstract : The critical size of Au nanoparticles for overcoming multi-drug resistance was identified to be between 4.1 nm and 5.4 nm. Abstract : Multidrug resistance (MDR) remains a huge obstacle during cancer treatment. One of the most studied MDR mechanisms is P-glycoprotein (P-gp) mediated drug efflux. Based on the three-dimensional structural characteristics of P-gp, gold nanoparticles (AuNPs) with average sizes of 4.1 nm and 5.4 nm were designed for the construction of nanodrug delivery systems (NanoDDSs), with the anticancer molecules 2-(9-anthracenylmethylene)-hydrazinecarbothioamide (ANS) and 6-mercaptopurine (6-MP) modified on the AuNP surfaces through the thiol group. In vitro cytotoxicity results suggested that the larger sized AuNPs can effectively decrease the drug resistance index of MCF-7/ADR cells to ∼2. Verapamil and P-gp antibody competitive experiments, combined with the cellular uptake of AuNPs, indicated that larger NanoDDSs were more conducive to intracellular drug accumulation and thus had improved anticancer activities, due to a size mismatch between the nanoparticles and the active site of P-gp, and, therefore, reduced drug efflux was seen. Measurements of ATPase activity and intracellular ATP levels indicated that the larger nanoparticles do not bind well to P-gp, thus avoiding effective recognition by P-gp. This was further evidenced by the observation that 4.1 nm and 5.4 nm NanoDDS-treated MCF-7/ADR cells showed remarkable differences in energy-related metabolic pathways. Therefore, the critical size of AuNPs for overcoming MDR was identified to be between 4.1 nm and 5.4 nm. This provides a more accurate description of the composite dimension requirements for NanoDDSs that are designed to overcome MDR.